Bibliometric analysis of Arabic Rhetoric in the translation and transcreation of literary texts - Al Zahrawi, Rasha T.; Syed Abdullah, Syed Nurulakla; Brahimi, Tayeb; Abdullah, Muhammad Alif Redzuan; Mustapha, Nik Farhan (Taylor & Francis Group, 2024)
In recent years, ‘transcreation’ has emerged in translation, integrating linguistic, cultural, and creative reinterpretation. With the rise of bibliometric analysis tools, mapping and assessing scientific activities across various fields have become possible, yet few studies apply these methods to translation. This study explores the developments and trends in transcreation within literary texts using quantitative and qualitative bibliometric analysis, particularly through VOSviewer. By analyzing 558 documents from the Scopus database focused on Arabic, rhetoric, transcreation, and translation, the study identifies the United States, United Kingdom, Jordan, Saudi Arabia, and Spain as the most active countries. The USA leads in total citations, followed by Saudi Arabia and the UK. King Saud University is highlighted as a leading institution. These findings provide a roadmap for future research and policy in applying Arabic rhetoric to the translation and transcreation of literary texts.